Algorithmic Authority and the Reconstitution of English Language Curriculum: A Critical Study of AI-Mediated Pedagogy - Abdul Wahab; L. Kerta Wijaya; Sarwadi Sarwadi (IJECA (International Journal of Education and Curriculum Application), 2026)
The integration of artificial intelligence (AI) in English language education has significantly transformed pedagogical practices and raised critical questions about authority, knowledge construction, and curriculum design. This study aims to examine how algorithmic authority reshapes the English language curriculum within AI-mediated pedagogical environments. Employing a critical qualitative case study design, The research applies Norman Fairclough’s Critical Discourse Analysis (CDA) model to explore power relations and knowledge production embedded in interactions among AI systems, teachers, and learners. Data were collected through curriculum document analysis using document analysis protocols, classroom observations using observation sheets, and in-depth interviews guided by semi-structured interview protocols. The findings reveal that AI-driven systems enhance personalization, efficiency, and accessibility, while simultaneously redistributing pedagogical authority from teachers to algorithmic systems. The study also identifies a paradox in which AI promotes learner autonomy but increases the risk of over-reliance and reduced critical engagement. In addition, issues of bias, inclusivity, and ethical accountability emerge due to standardized linguistic norms and opaque algorithmic processes. These findings imply that AI should be positioned not merely as a technical tool but as an epistemic agent that shapes curriculum and learning practices. Therefore, a balanced and human-centered pedagogical model is essential to ensure that technological innovation supports critical thinking, inclusivity, and meaningful learning.